Síndrome de burnout en médicos: el caso colombiano según revisión documental (2010 – 2021) - Ramos Pastrana, Stefania Del Carmen (Universidad Antonio Nariño, 2022)
The Burnout syndrome it's a psychological pathology caused for stressors in the work environment. It's characterized by affecting mainly 3 dimensions which, according to Burnout Maslach Invetory (MBI) are: Emotional exhaustion (EE), Despersonalization (DP), and Personal Accomplishment (PA). It occurs frecuently in highly demanding environments and by exposure to great emotional burdens such as occurs in the medical field, this will condition the quality of the service provided. Method: A documentary review of 27 articles was carried out that demostrate the reality of médical practice in the ibero - American context in a period of 11 years, focused especially on the Colombian context. The constant scarcity was observed in therms of the information available on this syndrome in medical personnel, sometimes generating even a single investigation per database